CONSISTENCY ANALYSIS OF PLANNING AND BUDGETING AND THEIR IMPLICATIONS ON PERFORMANCE ACHIEVEMENTS AT BAPPEDA OF NAGAN RAYA REGENCY - M. Ikmal Sarnando; Yasrizal Yasrizal (Jurnal Ilmiah Teunuleh, 2021)
This study aims to determine how consistent planning and budgeting is and aims to see performance achievements at the Regional Development Planning Agency of Nagan Raya Regency in 2018-2020. In calculating the suitability between programs and script activities carried out using the Consolidated Planning and Budgeting Matrix (MKPP) as well as the causes of non-synchronization between programs and activities between scripts carried out by detailed interviews. Obtaining requests for reading on orders between planning and budgeting manuscripts at Bappeda Kbaupaten Nagan Raya is adequate. The best fit is in the RKA and DPA texts. The cause of the inconsistency is caused by programs and activities that are not in sync with each other as well as technical obstacles in the field and the transfer of necessary central funds. The results of the analysis of performance in the Bappeda of Nagan Raya Regency as a whole, programs, and activities that have been determined.